and Its Organization - Tursunkhodzhaev Marat Lutfullaevich, (European Journal of Life Safety and Stability (2660-9630), 2023)
The position of regulation of social-labor relations in the article shows the urgency of forming an economic system of skilled labor in modern conditions. This need is necessary for a large part of the world community, including Uzbekistan. In Uzbekistan, mainly in the CIS countries, migration has become a natural phenomenon for the labor market. We can observe opposite trends in the manifestation of migration processes and social-labor relations in the national labor market.